The mediating roles of law legitimacy and police legitimacy in predicting cooperation with police in China - Li, Feng (Journal of criminology, 2021)
Public’s willingness to assist the police in preventing and fighting crime forms one of the fundamental pillars for implementing effective policing strategies and reforms. Despite widely supported by research conducted around the world, the process-based model of policing has received little research attention in authoritarian settings. Based on survey data collected from Shanghai, China, this study assesses the roles of law and police legitimacy in mediating the relationships between police fairness and effectiveness and willingness to cooperate with the police. We found that Chinese people’s greater senses of police fairness can lead to their higher levels of trust in and willingness to obey the police, but the total effect of police fairness on willingness to cooperate with the police is non-significant. Police effectiveness, meanwhile, directly promotes cooperation with the police. We also found that people who perceived the law as legitimate expressed greater willingness to cooperate with the police. Police legitimacy, compared to law legitimacy, is a more pronounced linking factor connecting police fairness to public cooperation. Implications for future research and policy are discussed.